Measuring process capability - Raneses, Nestor O. (Philippine Engineering Journal)
Process capability indices are succinct unitless statistical metric which measures the amount of common cause variation present in a process. They indicate the ability of the process to meet engineering specifications or whether process centering poses a problem. First and second generation indices : Cp, CpL, Cpu, Cpk, k, Cpm and Pearson process capability indices are presented, examined and compared. Single and confidence interval estimates of these indices are described. Finally, applications, drawbacks and uses of these indices are discussed.